(untitled) (Bucharest Working Papers in Linguistics, 2024)
The current paper analyzes Romanian predicate doubling, a construction that features topicalization of a non-finite form, a supine, that surfaces either as a bare verb or as a vP complete with arguments and adjuncts and is immediately followed by a clausal structure whose fully inflected tensed verb is the lexical copy of the supine. Predicate doubling occurs in a large variety of languages and has been used in syntactic research to support various theoretical accounts such the multiple copy theory of movement developed in Nunes (2004) or late adjunction of the arguments of the fronted predicate (Landau 2007), to name just a few. I argue for a base generation account of Romanian predicate doubling, drawing upon the framework implemented in Muñoz Pérez & Verdecchia (2022). This framework takes into consideration information structure and the way in which discourse develops by answering relevant questions under discussion.